2014
DOI: 10.2109/jcersj2.122.151
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and evaluation of hybrid materials from A-zeolite and ground glass powders for vitrified radioactive waste

Abstract: The samples from A-type zeolite and ground soda-lime glass powders were solidifed by calcinations at 600 to 800°C in air atmosphere. These hybrid zeolite/glass samples at 700°C were in part insufficiently densified and hybrid samples were fully densified at 800°C, although the densification was not generated at 600°C. A-zeolites were still stable in glass melt at 800°C for hybrid zeolite/glass samples. These hybrid zeolite/glass samples had the ion exchange ability of 20% against Sr 2+ and the high ability ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…zeolite in the hybrid materials. This evolution of removal rate is similar to that reported by Kamitani et al 7) using A-type zeolite materials, with our study showing higher removal rates. The hybrid materials with X-type zeolite showed different removal rates compared with the other hybrid materials, especially for zeolite content greater than 20%.…”
Section: )4)supporting
confidence: 92%
See 2 more Smart Citations
“…zeolite in the hybrid materials. This evolution of removal rate is similar to that reported by Kamitani et al 7) using A-type zeolite materials, with our study showing higher removal rates. The hybrid materials with X-type zeolite showed different removal rates compared with the other hybrid materials, especially for zeolite content greater than 20%.…”
Section: )4)supporting
confidence: 92%
“…Kamitani et al have reported that a pellet-like sample of hybrid materials of soda-lime glass and A-type zeolite can remove cesium and strontium ions. 7) Although hybrid materials from zeolites and soda-lime glass are interesting and attractive as an ion-exchange material, there is no report on hybrid materials using other types of zeolites. The Si/Al ratio of A-type zeolite is equal to 1, which is the minimum value for zeolites.…”
Section: )4)mentioning
confidence: 99%
See 1 more Smart Citation
“…2 (a). Previous papers report that the existence of Ca enhance the formation of calcium aluminate and subsequently inhibit the formation of useful A type zeolite on the hydrothermal treatments [14][15][16]. It is thought that this reason is because calcium aluminate was not generated since Ca content was removed by pretreatment.…”
Section: Resultsmentioning
confidence: 99%